Environmental effects on fruit composition of cloudberry/bakeapple ( Rubus chamaemorus L.) grown in southern Labrador, Canada - Li, Jiabai; Percival, David; Hoyle, Jeff; Yue, Jin; White, Jane; Head, Krista; Pruski, Kris (Canadian Journal of Plant Science, 2015)
Li, J., Percival, D., Hoyle, J., Yue, J., White, J., Head, K. and Pruski, K. 2015. Environmental effects on fruit composition of cloudberry/bakeapple (Rubus chamaemorus L.) grown in southern Labrador, Canada. Can. J. Plant Sci. 95: 1167–1175. The composition of fruit collected from three fields located near Lanse'au Clair, Red Bay and Cartwright in southern Labrador, Canada, was analyzed over the 2011 and 2012 growing seasons. Soluble solids, titratable acidity, total phenolics, total anthocyanins, chlorogenic acid, caffeic acid, quercetin-3-glucoside, cyanidin-3-glucoside and ellagic acid were determined after each harvest using standard laboratory procedures. Temperature, precipitation, wind and other environmental factors affected growth and deposition of nutrients in harvested fruit. Soluble solids content (TSS), titratable acidity (TA), total anthocyanin, chlorogenic acid, cyanidin, total phenolic compounds and total anthocyanins of cloudberry fruit were significantly (P<0.05) affected by the combination of the growing season and the location. The TSS, TA and total phenolics were higher in fruits from Cartwright (most northern location) in both seasons compared with the other two locations. The HPLC analysis of compounds showed the ellagic acid and quercetin 3-o-β-D-glucoside contents of fruits were significantly affected by the location and the growing season (higher in 2012 compared with 2011), while contents of chlorogenic acid, caffeic acids, and cyanidin-3-o-β-glucoside were not. To our knowledge this is the most comprehensive study of fruit composition of bakeapple conducted in southern Labrador, Canada.